2018
DOI: 10.21873/anticanres.12637
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Platinum-based Chemotherapy Followed by Radical Hysterectomy for Stage Ib2-IIb Adenocarcinoma of the Uterine Cervix – An Italian Multicenter Retrospective Study

Abstract: Abstract. Aim: To assess the patterns of recurrence and clinical outcomes of patients with cervical adenocarcinoma who underwent neoadjuvant platinum-based chemotherapy (NACT) followed by radical hysterectomy. Patients andConcurrent cisplatin-based chemotherapy and radiotherapy (CCRT) is the standard-of-care for patients with locally advanced cervical cancer and recent meta-analyses of randomized trials have confirmed that this therapeutic approach significantly improves progression-free survival and overall s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…Sixteen studies were included in the systematic review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 12 studies in the meta-analysis [15][16][17][18][19][20][23][24][25][27][28][29][30]. Fifty-one studies assessed for eligibility were excluded after applying our exclusion criteria, i.e., the same cohort as a study already included across multiple papers (n = 1), <2 events (N = 4), <10 cases (n = 2), evaluation of clinical rather than pathological response (n = 27), HR with 95% CI not extractable (n = 15), review (n = 2).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen studies were included in the systematic review [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] and 12 studies in the meta-analysis [15][16][17][18][19][20][23][24][25][27][28][29][30]. Fifty-one studies assessed for eligibility were excluded after applying our exclusion criteria, i.e., the same cohort as a study already included across multiple papers (n = 1), <2 events (N = 4), <10 cases (n = 2), evaluation of clinical rather than pathological response (n = 27), HR with 95% CI not extractable (n = 15), review (n = 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…Eight studies (50%) dichotomized pathological response as "optimal" (complete response or residual with <3 mm stromal invasion) vs. "suboptimal" (residual with >3 mm stromal invasion) [17,19,21,[23][24][25][26]29]; two studies (12.50%) assessed the proportion of viable cells (<1/3, 1/3-to-2/3 or >2/3) [15,20]; two studies (12.50%) assessed the diameter of the residual tumor (cut-offs at 1 mm or 5 mm) [16,18]; two studies (12.50%) dichotomized pathological response as complete disappearance of the tumor vs. any residual [23,30]; one study (6.25%) dichotomized the residual tumor as intracervical vs. extracervical [27]; the remaining study (6.25%) adopted several systems simultaneously, proposing a combined score [22]. Seven studies (43.75%) assessed OS [15][16][17][18][19][20]30], one (6.25%) assessed PFS [24], and eight (50%) assessed both OS and PFS [21][22][23][24][25][26][27][28][29]. Characteristics of the included studies are reported in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Compared with RS alone, especially compared with CCRT, NACT + RS may improve the long-term disease-free survival rate and overall survival rate of patients with locally advanced cervical cancer stage IB2-IIB [ 7 ]. Moreover, total hysterectomy after NACT may be an option for patients with stage Ib2-IIb cervical adenocarcinoma [ 46 ]. However, this study found that NACT did not improve overall survival, but reduced the number of patients receiving postoperative radiotherapy [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on OCTA imaging is available elsewhere. 19,23,24 The optical microangiographycomplex algorithm analyzed the changes in complex signals (both phase and intensity changes contained within sequential B-scans obtained at the same position), and then generated en face microvascular images of the SVC, which spanned from the inner limiting membrane to the posterior surface of the inner-plexiform layer. The AngioPlex incorporates the FastTrac retinal tracking technology to minimize motion artifacts.…”
Section: Octa Imagingmentioning
confidence: 99%